Microbial Biocatalysis - Wang, Zhilong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Biocatalysis is a sustainable alternative for the chemical industry in manufacturing, monitoring, and waste management. Biocatalytic processes perform with isolated enzymes or whole cells as biocatalysts. Whole-cell biocatalysts offer some unique advantages of cascade reactions catalyzed by multienzymes as well as a single bioredox reaction with cofactor regeneration in a single strain. Therefore, whole-cell biocatalysts are widely applied for biosynthesis/biotransformation to produce value-added chemicals as well as the complete mineralization of organic pollutants.Biological catalytic processing using whole-cell biocatalysts includes biocatalyst engineering, bio-reaction engineering, and downstream processing. In addition to the traditional screening of microbial strains and immobilized whole-cell biocatalysts, modern genetic engineering, metabolic engineering, and synthetic biology make tailored whole-cell biocatalysts possible. At the same time, some integrated processes have successfully been applied in the catalytic processing using living whole-cell biocatalysts, such as harnessing biocompatible chemistry to interface with the microbial metabolism as well as using various separation techniques for in situ product removal.This reprint on “Microbial Biocatalysis” provides a comprehensive overview of the recent developments of catalyst discovery, catalyst modification, and process intensification for whole cell catalysis in fermentation, biotransformation or biodegradation processes.